Recollecting The Unforgettable: Interrogating Migration, Trauma and Identity In Select Tripura Bengali Poems - Chakraborty, Jagriti; Chakrabarty, Madhumita (International Journal of Membrane Science and Technology, 2023)
The human mind retains the sequences of episodes that include prior experiences, memories and narratives. The traumatic memories of past are the one which stays in the subconscious and the recollection of those events formulates images of terror. Partition of India is one such event which incorporates narratives of multiple experiences of migration and separation. Tripura a small hilly state of North East India has seen the flood of migrants even before the major India Pakistan division took place. Most of Bengalis settled in Tripura have their roots in East Pakistan or which is after 1971 known as Bangladesh. Many decades have passed but they are still carrying their stories of migration and passing it to generation after generation. The trauma of separation from homeland becomes part of their memory and gets registered by the help of literature. This paper aims to examine select poems of Tripura which focuses upon the relation of migration and memory.